Growth and nutritional diagnosis of Rosemary plants submitted to nitrogen and sulfate fertilization - Souza, Aline dos Anjos; dos Santos, Anacleto Ranulfo; de Souza, Girlene Santos; de Jesus, Railda Santos; Lima, Janderson do Carmo; Oliveira, Uasley Caldas de (Comunicata Scientiae, 2020)
Studies on the cultivation of medicinal plants are of relevance to the population since they are primary sources of medication. Among these plants stands out the rosemary (Rosmarinus officinalis L.) for having diverse therapeutic properties. The objective of this work was to evaluate the initial growth and nutritional status of rosemary plants grown with different co’ncentrations of nitrogen and sulfur. The treatments were distributed in a 4x2 factorial scheme with four nitrogen doses: 105, 210, 315, and 420 mg L-1 of nitrogen combined with two sulfur doses: 32 and 64 mg L-1 with seven replications totaling 56 experimental units. The seedlings were obtained through asexual propagation (cuttings), originating from parent plants. The experimental units were arranged in a completely randomized design. Growth evaluations were carried out at 120 days of cultivation, using: plant height (HT) stem diameter (DS), root dry matter mass (RDM), stem dry matter mass (SDM), mass leaf dry matter (LDM), total dry matter (TDM), shoot dry matter mass (SDMS). The data obtained were subjected to analysis of variance and depending on the level of significance in the F test, the study was carried out using the means test (Tukey 5%). The agronomic characteristics (HT), (DS), (RDM) and (MDMAP) were significant for N. Only (RDM) showed significant interaction for the doses of N and S. The dose 420 mg L-1 promoted the highest concentrations in the components leaf and stem. The lowest dose 105 mg L-1, N promoted the highest concentrations of S in the leaf and stem. The assimilation of S by the rosemary plants was dependent on the doses of N.